(untitled) - Morrison, Robert Thornton (Boston, 1966)
The book is divided into various chapters that talks about the various aspects of this branch. The chapters include fundamental of organic chemistry, specific topics, chemistry of functional groups, contemporary and future organic chemistry, and biomolecules and bioorganic chemistry
Keywords: Chemistry, Organic,Hóa học, hữu cơ